Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja pada CV Bumi Mandiri Sejahtera Karawaci Tangerang - Septriansyah, Farhan; Lesmana, Ihwan Satria; Romli, Ombi (BISMA : Business and Management Journal, 2024)
A good work environment and work motivation will be one of the motivating factors for employees to carry out their work optimally. On the other hand, organizations need a safe and comfortable work environment and good work motivation from both the company and the work leaders which aims to increase work productivity. The purpose of this study is to determine the effect of the work environment and work motivation on work productivity at CV Bumi Mandiri Sejahtera Karawaci Tangerang. The research method used by the author is the causal associative method with a quantitative descriptive approach, where the process of taking samples from a population and using a questionnaire as the main data collection tool. The data collection technique used a questionnaire to 58 (fifty eight) respondents with Likert scale measurements and using the help of SPSS version 26. The results of this study indicate that (1) partially, the work environment significantly influences work productivity at CV Bumi Mandiri Sejahtera Karawaci Tangerang (2) Partially, work motivation significantly influences work productivity at CV Bumi Mandiri Sejahtera Karawaci Tangerang and simultaneously, the work environment and work motivation significantly influence work productivity at CV Bumi Mandiri Sejahtera Karawaci Tangerang. Based on the results of the study, both partially and simultaneously, the work environment and work motivation significantly influence work productivity at CV Bumi Mandiri Sejahtera Karawaci Tangerang